The Analysis Of Compensation Impact To Job Productivity - BAMBANG WAHYUDI WICAKSONO; RISKA KUSUMA PUTRI (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2013)
ABSTRACT The objective of this study was to find out the impact of compensation to ward job performance the population of this study was PT.Federal Izumi manufacturing Jakarta. Meanwhile the sample was the staff of PT.Federal Izumi manufacturing with the number 110 staff. The sample was taken though Random Sampling. In analysing the data, then linear regression was used by using SPSS program. It was found that there was significant impact between direct compensation toward job performance which was shown by the significant value 0,003<0,05 and there was significant impact toward indirect compensation toward job performance was shown by the value 0,00 which is lower than 0,05. Mean while, to find out the impact of direct compensation and indirect compensation toward the job performance, multiple regression was used. Based on SPSS analysis, it was found there was significant correlation which was shown by the value F 0,00 which was lower than 0,005.